2012
DOI: 10.1007/s00223-012-9576-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bone Strength is Dependent on Skeletal Site in Disuse Osteoporosis in Rats

Abstract: Intramuscular injection with botulinum toxin A (BTX) leads to a transient paralysis of the muscles, resulting in a rapid loss of muscle mass and function as well as rapid bone loss (disuse osteoporosis). The purpose of this study was to investigate the temporal development and the site specificity of BTX-induced immobilization on bone strength at five skeletal sites. Three-month-old rats (n = 108) were randomized into nine groups: one served as baseline, while four were injected with BTX and four with saline i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
4
27
0
Order By: Relevance
“…The tail-suspended animal model has been widely accepted as an effective disuse osteoporosis model for simulating bone loss [15,22,41]. In the current tail suspension experiment, bone formation was mildly inhibited and bone resorption was markedly increased in unloaded mice, these 20 changes are in accord with previous study [14,[42][43][44]. Our correlation analysis and linear regression showed that the expression level of p-eIF2α was positively associated with the number of bone-forming osteoblasts, and negatively associated with that of bone-resorbing osteoclasts.…”
Section: Discussionsupporting
confidence: 85%
“…The tail-suspended animal model has been widely accepted as an effective disuse osteoporosis model for simulating bone loss [15,22,41]. In the current tail suspension experiment, bone formation was mildly inhibited and bone resorption was markedly increased in unloaded mice, these 20 changes are in accord with previous study [14,[42][43][44]. Our correlation analysis and linear regression showed that the expression level of p-eIF2α was positively associated with the number of bone-forming osteoblasts, and negatively associated with that of bone-resorbing osteoclasts.…”
Section: Discussionsupporting
confidence: 85%
“…We have previously shown losses of bone density, microstructure, and strength in rats following BTX injection (Vegger et al, 2014, Thomsen et al, 2012, Brüel et al, 2013, Grubbe et al, 2014), and these findings are similar to what has been shown in mice (Warner et al, 2006a, Warden et al, 2013, Ellman et al, 2014, Manske et al, 2010a, Aliprantis et al, 2012, Grimston et al, 2007, Ausk et al, 2013, Manske et al, 2010b, Manske et al, 2012, Poliachik et al, 2010, Warner et al, 2006b). Furthermore, it has been demonstrated that the bone deterioration following BTX-induced muscle paralysis is paralleled by an increase in osteoclast activity and osteoclastogenesis, and these two factors are believed to play key roles for the rapidly occurring bone loss in this model of immobilization (Aliprantis et al, 2012, Warner et al, 2006b).…”
Section: Introductionsupporting
confidence: 80%
“…The bone samples were obtained from 4-months-old female Wistar rats used as controls in previous studies (Bach-Gansmo et al, 2013;Thomsen et al, 2012). The animals were sacrificed, the hind legs removed, and the femora were carefully cleaned.…”
Section: Animalsmentioning
confidence: 99%
“…The femora had previously been used for ascertaining bone strength using three point bending tests (Thomsen et al, 2012) and were cut into rods for SR µCT investigations. The proximal half of femurs were embedded in Epofix (Struer, Ballerup, Denmark) and rectangular bone bars were cut from the femoral mid-diaphysis using a water cooled Exakt 300 CL diamond band saw (Exakt Apparatebau, Norderstedt, Germany).…”
Section: Synchrotron Radiation Micro Computed Tomography (Sr µCt)mentioning
confidence: 99%